Osseous sarcoidosis presenting as lytic and blastic bone lesions: A rare diagnostic challenge - J. Bastidas; L. López-Nuñez; R. Faré; Javier G. Moríñigo; I. Ros; A. Juan Mas (Radiology Case Reports)
Osseous sarcoidosis is a rare manifestation of sarcoidosis, often mimicking other conditions like metastatic disease. Skeletal involvement occurs in only 3%-13% of cases (1), making diagnosis challenging. We present the case of a 63-year-old female with a 1-month history of inflammatory bone pain and multiple lytic and blastic lesions.A 63-year-old female presented with a 1-month history of inflammatory pain in the left hip and lumbar spine. Radiological studies, including magnetic resonance imaging (MRI) and computed tomography (CT), revealed multiple bone lesions throughout the lumbar spine, sacrum and iliac bones, raising suspicion of metastatic disease a bone biopsy confirmed a diagnosis of sarcoidosis.MRI and CT showed lytic and blastic lesions in the axial skeleton, with FDG-PET indicating diffuse uptake in the iliac bone and mediastinal adenopathy. Imaging was crucial in ruling out metastases and guiding the biopsy, which confirmed the diagnosis.Osseous sarcoidosis is a rare entity that poses a significant diagnostic challenge, often resembling metastatic disease. Imaging techniques such as MRI and CT, combined with biopsy, are effective, noninvasive methods for evaluation and diagnosis. The patient was treated with corticosteroids in high doses and systemic methotrexate, showing improvement in inflammatory pain and stabilization of the bone lesions.